Learning does not end in the lecture hall - Abd Razak, Dzulkifli (2006)
Universities are charged with nurturing a ’first class mentality’. For this to happen, universities must be allowed to function without outside intrusions. IT is a relief that the situation over the socalled "textbook" on ethnic relations in a university has been defused. But a textbook it was not. It was more a course guide or outline of sorts. At best, it as an unfinished lecture note confined to the university. If at all it was to be used as a "textbook", many could be unaware that at tertiary level, there is no one "textbook" that suffices, unlike in schools. University students are exposed to a wide array of scholarly works so that they can be well educated in a particular subject.